La crítica de la economía política como crítica a lasubjetividad en Marx - Nación Pantigoso, Miguel Ángel (2025)
Marx’s critique of political economy consists of a critique of alienation. The purpose of this article is to argue the existence of a materialist connection between alienation and ideology in Marx. The study engages with Louis Althusser’s influential thesis, which suggests that the concept of alienation is ideological, as it is based on an idealist notion of subjectivity opposed to the material relations of production. However, Marx does not discard the concept; instead, he transforms it in a materialist sense, conceiving of the subject in relation to the object. Unlike the consciousness-based philosophies of Hegel and Feuerbach, Marxist alienation is defined as the privation of the producer from the objective and material links to the means, conditions, and product of their labor. This material dispossession prevents the subject’s realization and results in the worker being reduced to abstract labor capacity. The critique of ideology, developed in The German Ideology, exposes how the ideological notion of abstract and universal subjectivity, perpetuated by bourgeois political economy, conceals the limiting material relations and allows for the reproduction of the worker’s dispossession.